Congenital fibrinogen disorders: a retrospective clinical and genetic analysis of the Prospective Rare Bleeding Disorders Database - Mohsenian, Samin; Palla, Roberta; Menegatti, Marzia; Cairo, Andrea; Lecchi, Anna; Casini, Alessandro; Neerman-Arbez, Marguerite; Asselta, Rosanna; Scardo, Sara; Siboni, Simona Maria; Blatny, Jan; Zapletal, Ondrej; et al. (Blood advances, 2024)
Congenital fibrinogen deficiency (CFD) is a rare bleeding disorder caused by mutations in FGA, FGB, and FGG. We sought to comprehensively characterize patients with CFD using PRO-RBDD (Prospective Rare Bleeding Disorders Database). Clinical phenotypes, laboratory, and genetic features were investigated using retrospective data from the PRO-RBDD. Patients were classified from asymptomatic to grade 3 based on their bleeding severity. In addition, FGA, FGB, and FGG were sequenced to find causative variants. A total of 166 CFD cases from 16 countries were included, of whom 123 (30 afibrinogenemia, 33 hypofibrinogenemia, 55 dysfibrinogenemia, and 5 hypodysfibrinogenemia) were well characterized. Considering the previously established factor activity and antigen level thresholds, bleeding severity was correctly identified in 58% of the cases. The rates of thrombotic events among afibrinogenemic and hypofibrinogenemic patients were relatively similar (11% and 10%, respectively) and surprisingly higher than in dysfibrinogenemic cases. The rate of spontaneous abortions among 68 pregnancies was 31%, including 86% in dysfibrinogenemic women and 14% with hypofibrinogenemia. Eighty-six patients received treatment (69 on-demand and/or 17 on prophylaxis), with fibrinogen concentrates being the most frequently used product. Genetic analysis was available for 91 cases and 41 distinct variants were identified. Hotspot variants (FGG, p.Arg301Cys/His and FGA, p.Arg35Cys/His) were present in 51% of dysfibrinogenemia. Obstetric complications were commonly observed in dysfibrinogenemia. This large multicenter study provided a comprehensive insight into the clinical, laboratory, and genetic history of patients with CFDs. We conclude that bleeding severity grades were in agreement with the established factor activity threshold in nearly half of the cases with quantitative defects.
Keywords: Humans; krvácení; prospektivní studie; Afibrinogenemia; Hemostatics; retrospektivní studie; ženské pohlaví; hemostatika; Female; fibrinogen; Fibrinogen; afibrinogenemie; Hemorrhage; Retrospective Studies; lidé; Prospective Studies